Emergence Of Consciousness And Qualia From A Complex Brain - Korf Jakob (Folia Medica, 2014)
Qualia are private conscious experiences of which the associated feelings can be reported to other people. Whether qualia are amenable to scientific exploration has often been questioned, which is challenged by the present article. The following arguments are given: 1. the configuration of the brain changes continuously and irreversibly, because of genetic and environmental influences and interhuman communication; 2. qualia and consciousness are processes, rather than states; 3. private feelings, including those associated with qualia, should be positioned in the context of a personal brain as being developed during life; 4. consciousness and qualia should be understood in the context of general system theory, thus concluding that isolated, in vitro, properties of neurons and other brain constituents might marginally contribute to the understanding of higher brain functions, mind or qualia; 5. current in vivo approaches have too little resolution power - in terms of space and time - to delineate individual and subjective brain processes.